A potential cephalopod from the early Cambrian of eastern Newfoundland, Canada - Hildenbrand, Anne; Austermann, Gregor; Fuchs, Dirk; Bengtson, Peter; Stinnesbeck, Wolfgang (Communications biology, 2021)
Although an early Cambrian origin of cephalopods has been suggested by molecular studies, no unequivocal fossil evidence has yet been presented. Septate shells collected from shallow-marine limestone of the lower Cambrian (upper Terreneuvian, c. 522 Ma) Bonavista Formation of southeastern Newfoundland, Canada, are here interpreted as straight, elongate conical cephalopod phragmocones. The material documented here may push the origin of cephalopods back in time by about 30 Ma to an unexpected early stage of the Cambrian biotic radiation of metazoans, i.e. before the first occurrence of euarthropods.
Gesehen am 24.03.2021